2015
DOI: 10.1016/j.immuni.2014.12.016
|View full text |Cite
|
Sign up to set email alerts
|

The RNA Sensor RIG-I Dually Functions as an Innate Sensor and Direct Antiviral Factor for Hepatitis B Virus

Abstract: Host innate recognition triggers key immune responses for viral elimination. The sensing mechanism of hepatitis B virus (HBV), a DNA virus, and the subsequent downstream signaling events remain to be fully clarified. Here we found that type III but not type I interferons are predominantly induced in human primary hepatocytes in response to HBV infection, through retinoic acid-inducible gene-I (RIG-I)-mediated sensing of the 5'-ε region of HBV pregenomic RNA. In addition, RIG-I could also counteract the interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
358
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 371 publications
(374 citation statements)
references
References 48 publications
9
358
2
5
Order By: Relevance
“…However, several published studies have recently investigated and characterized HBV infection in vitro models and have provided evidence for activation of innate immune pathways (25,30). We therefore endeavored to investigate this by focusing on very early time points after simulation with HBV and DNA-driven innate immune pathways that may play a role in HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, several published studies have recently investigated and characterized HBV infection in vitro models and have provided evidence for activation of innate immune pathways (25,30). We therefore endeavored to investigate this by focusing on very early time points after simulation with HBV and DNA-driven innate immune pathways that may play a role in HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Retinoic acid inducible gene-I (RIG-I) and melanoma differentiation antigen (MDA)-5 are cytosolic molecules that sense double-stranded (ds) RNA as a virus replicative intermediate that subsequently activates the interferon regulatory transcription factor-3 (IRF-3) and NF-kappaB (NF-jB) pathways [20]. The 5 0 -e region of pregenomic HBV RNA has recently been reported to be recognizable by RIG-I in hepatocytes, which subsequently stimulates IFN-k release [21]. RIG-I was also found to exert a direct suppressive effect on HBV replication by interfering with the binding of HBV polymerase to pregenomic RNA [21].…”
Section: Pattern Recognition Receptors In Hbv Infectionmentioning
confidence: 99%
“…The 5 0 -e region of pregenomic HBV RNA has recently been reported to be recognizable by RIG-I in hepatocytes, which subsequently stimulates IFN-k release [21]. RIG-I was also found to exert a direct suppressive effect on HBV replication by interfering with the binding of HBV polymerase to pregenomic RNA [21]. To date, limited information is available regarding which HBV components stimulate relevant PAMP receptors.…”
Section: Pattern Recognition Receptors In Hbv Infectionmentioning
confidence: 99%
“…Human hepatitis B virus (HBV) has its ability to escape the host immune system. [16][17][18] Here, we found that Rubicon can be induced by infection by viruses such as HBV, enterovirus 71 (EV71), influenza A virus (IAV) and vesicular stomatitis virus (VSV) and was a negative regulator for distributed IRF3 activation, IFN induction, and cellular antiviral response. Rubicon interacted with NEMO and suppressed TBK1 phosphorylation.…”
Section: Introductionmentioning
confidence: 99%